Association between serum uric acid-to-high-density lipoprotein cholesterol ratio and metabolic dysfunction-associated steatotic liver disease among Chinese children with obesity - Liu, Meijuan; Cao, Bingyan; Luo, Qipeng; Song, Yanning; Liu, Kai; Wu, Di (Frontiers in Endocrinology, 2025)
BackgroundMetabolic dysfunction-associated steatotic liver disease (MASLD) has become one of the most prevalent chronic liver diseases worldwide. The serum uric acid-to-high-density lipoprotein cholesterol ratio (UHR) has been recognized as a novel marker for metabolic diseases, including MASLD. However, all previous studies were performed in adults.ObjectivesTo explore the relationship between the UHR and MASLD in Chinese children with obesity.MethodsA retrospective study was conducted including 1284 obese children hospitalized at Beijing Children’s Hospital between January 2016 and December 2022. Logistic regression analysis and restricted cubic splines were performed to assess the association between the UHR and the odds of MASLD. The receiver operator characteristic (ROC) curve analysis was used to estimate the diagnostic value of UHR for MASLD in children with obesity.ResultsThe prevalence of MASLD was high, which reached 61.76% in children with obesity. UHR levels were higher in obese children with MASLD than those with non-MASLD for both genders. After dividing all individuals into three groups according to the tertiles of UHR, the prevalence rate of MASLD increased progressively from the tertile 1 to tertile 3 of UHR (34.11% vs. 70.56% vs. 80.61%). Logistic regression analysis showed that obese children with higher UHR levels were significantly associated with MASLD risk, independent of confounding factors such as age, gender, body mass index (BMI), fasting blood glucose (FBG), alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), and creatinine (Cr). The non-linear relationship analysis demonstrated that a UHR between approximately 300 and 900 suggested a saturation effect of MASLD risk. ROC analysis indicated that UHR might serve as a predictive marker for diagnosing MASLD in obese children.ConclusionsIn children with obesity, UHR is significantly associated with MASLD and might serve as a novel and useful predictor for MASLD onset.